2013
DOI: 10.1016/j.ejrad.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal MRI at 3.0T and 7.0T: A comparison of relaxation times and image contrast

Abstract: OBJECTIVE The purpose of this study was to measure and compare the relaxation times of musculoskeletal tissues at 3.0T and 7.0T, and to use these measurements to select appropriate parameters for musculoskeletal protocols at 7.0T. MATERIALS AND METHODS We measured the T1 and T2 relaxation times of cartilage, muscle, synovial fluid, bone marrow and subcutaneous fat at both 3.0T and 7.0T in the knees of five healthy volunteers. The T1 relaxation times were measured using a spin-echo inversion recovery sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 15 publications
7
53
0
Order By: Relevance
“…It is to note that the visibility of the larger anatomical structures, such as the mandibular condyle, mandibular fossa and inferior pterygoid muscle did not benefit from imaging at 7.0 T. These results are well in line with the assumption that fine anatomical structures cannot be depicted in full detail at 3.0 T, 7,12,19 whereas larger structures do not necessarily benefit from a higher spatial resolution. This observation also might explain why the overall image quality was rated similar for both field strengths.…”
Section: Qualitative Analysissupporting
confidence: 77%
See 3 more Smart Citations
“…It is to note that the visibility of the larger anatomical structures, such as the mandibular condyle, mandibular fossa and inferior pterygoid muscle did not benefit from imaging at 7.0 T. These results are well in line with the assumption that fine anatomical structures cannot be depicted in full detail at 3.0 T, 7,12,19 whereas larger structures do not necessarily benefit from a higher spatial resolution. This observation also might explain why the overall image quality was rated similar for both field strengths.…”
Section: Qualitative Analysissupporting
confidence: 77%
“…When assessing a new sequence with respect to a potential clinical application at a new field strength, it is inherently necessary to optimize the imaging protocol with respect to the different relaxation times of musculoskeletal tissue at different static magnetic field strengths. 19 In the current study, selected sequence parameters, such as TE and TR have been chosen to fit different T 1 and T 2 values of specific tissues. However, it is to note that the TMJ consists of various tissue types with a heterogeneous difference between relaxation times at two different field strengths.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38][39][40][41][42][43][44] Additionally, concentration of other molecules relevant to lymphatic function will influence the water T 2 . It has been shown that in agarose phantoms water T 2 increases with increasing levels of NaCl.…”
Section: Physiology Of Deep and Superficial T 2 Changesmentioning
confidence: 99%